Civil Law Aspects of Crypto Investment Dispute Resolution Through Arbitration and Litigation - Handro Kurnia Sitorus; Ahyar Dinda Alamsyah Harahap; Abdul Latif; Aripa Syawalia; Indra Utama Tanjung (ISNU Sumatera Utara, 2025)
Digital transformation in the financial sector has given birth to new investment instruments in the form of crypto assets based on blockchain technology. Despite its great potential, crypto investment also gives rise to various civil disputes between investors and service provider platforms. Such disputes are often caused by defaults, unlawful acts, or losses due to digital system failures, which have not been specifically regulated in national law. This research aims to identify the form of civil law relationships in crypto transactions, examine the types of disputes that arise, and evaluate the effectiveness of two dispute resolution mechanisms, namely arbitration and litigation. The method used is a normative juridical approach through literature studies that include laws and regulations, scientific literature, as well as court and arbitration decisions. The results of the study show that arbitration has advantages in terms of efficiency and flexibility, but faces obstacles in enforcing cross-jurisdictional awards. In contrast, litigation provides stronger formal legal guarantees, but tends to be slow and less adaptive to technological aspects. The main obstacles faced are the absence of substantive regulations, limitations in digital proof, and low technical literacy of legal apparatus. Therefore, regulatory reform and institutional capacity strengthening are needed to ensure equal legal protection for crypto investors in Indonesia.